2017
DOI: 10.1096/fj.201700071r
|View full text |Cite
|
Sign up to set email alerts
|

Tendon stem/progenitor cells regulate inflammation in tendon healing via JNK and STAT3 signaling

Abstract: Tendon stem/progenitor cells (TSCs) have been found in different anatomic locations and showed a promising regenerative potential. We identified a role of TSCs in the regulation of inflammation during healing of acute tendon injuries. Delivery of connective tissue growth factor (CTGF) into full-transected rat patellar tendons significantly increased the number of CD146 + TSCs, leading to enhanced healing. In parallel, CTGF delivery significantly reduced the number of iNOS + M1 macrophages and increased the exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
69
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 70 publications
(76 citation statements)
references
References 53 publications
3
69
0
Order By: Relevance
“…Persistently active STAT3 has been identified in many human cancers and appears to be required for the continued growth or resistance to apoptosis of cultured human cancer cells. 20,25,41,42 In this study, phospho-JNK activation in- Additionally, several reports have demonstrated that there are interacting regions in STAT3 and c-Jun that participate in cooperative transcriptional activation. 14,18,19,43 These concepts support our finding that phospho-STAT3 was suppressed by the activation of phospho-JNK and phospho-c-Jun.…”
Section: Discussionmentioning
confidence: 65%
See 2 more Smart Citations
“…Persistently active STAT3 has been identified in many human cancers and appears to be required for the continued growth or resistance to apoptosis of cultured human cancer cells. 20,25,41,42 In this study, phospho-JNK activation in- Additionally, several reports have demonstrated that there are interacting regions in STAT3 and c-Jun that participate in cooperative transcriptional activation. 14,18,19,43 These concepts support our finding that phospho-STAT3 was suppressed by the activation of phospho-JNK and phospho-c-Jun.…”
Section: Discussionmentioning
confidence: 65%
“…Our research team has reported that inhibition of STAT3 phosphorylation has beneficial clinical therapeutic effects on human osteosarcoma. Persistently active STAT3 has been identified in many human cancers and appears to be required for the continued growth or resistance to apoptosis of cultured human cancer cells . In this study, phospho‐JNK activation induced significant phospho‐STAT3 degradation.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…While this review focused on TSPCs since these tissue‐specific cells may be “primed” toward tenogenic differentiation, pioneering early research in tendon tissue engineering applied bone marrow‐derived mesenchymal stem cells and tested strategies for optimizing their tenogenic potential via 3‐dimensional and mechanical cues . Recent studies also highlight the exciting capacity of neighboring endogenous cells to be activated and recruited toward tendon repair in vivo, given the correct molecular signals . The choice of cell type is an essential consideration which impacts the overall therapeutic strategy.…”
Section: Therapeutic Strategies For Tendon Repairmentioning
confidence: 99%
“…16 Furthermore, a biocompatible delivery system is required to positively impact the repairing tendon stumps, while avoiding negative inflammatory reactions that lead to the formation of adhesions, gap formation, and/or repair rupture. 17 The current study aimed to address limitations of previous biological interventions for intrasynovial flexor tendon repair by combining CTGF, a growth factor recently shown to promote tendon regeneration in rodents, [18][19][20] with a novel porous suture delivery method. 21 Lee et al recently demonstrated that CTGF embedded in a fibrin matrix can enrich tendonresident CD146 þ stem/progenitor cells and promote neovascularization, tenogenic differentiation, collagen deposition, and matrix remodeling in a rat patellar tendon surgical model.…”
mentioning
confidence: 99%